Effect of berberine and (+/-)-bicuculline isolated from Corydalis chaerophylla on spore germination of some fungi - Basha, S Ameer; Mishra, R K; Jha, R N; Pandey, V B; Singh, U P (Folia microbiologica, 2002)
Berberine and (+/-)-bicuculline were isolated from roots and leaves, respectively, of Corydalis chaerophylla. Both were effective in vitro against spore germination of some plant pathogenic fungi (Alternaria brassicicola, A. brassicae, A. cheiranthi, A. melongenae, A. solani, Colletotrichum musae, C. falcatum, Curvularia penniseti, C. lunata, C. maculans, C. pallescens, Curvularia sp., Erysiphe pisi, E. cichoracearum, Erysiphe sp., Fusarium udum, Helminthosporium spiciferum, H. penniseti, H. frumentacei, Heterosporium sp., Oidium erysiphoides and Ustilago cynodontis). Berberine and (+/-)-bicuculline significantly inhibited spore germination of all the fungi at concentrations of 100-1000 ppm. Berberine was effective against all the fungi at all concentrations; most of the fungi did not germinate at 1000 ppm. H. penniseti conidia did not germinate at any concentration of (+/-)-bicuculline. U. cynodontis was the least sensitive fungus at lower concentrations but 800 ppm dose was highly effective.
Keywords: Spores, Fungal; Corydalis; Bicuculline; berberin; Plants, Medicinal; bikukulin; antifungální látky; léčivé rostliny; Antifungal Agents; spory hub; Berberine